Optimization of The Smallest Road Using The Traveling Salesman Problem (TSP) Method - Alvendo Wahyu Aranski (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Optimization is the process of obtaining a minimum (small) or maximum (largest) value in an opportunity function. One case that uses the optimization function is the Traveling Salesman Problem (TSP). The case study problem in this research is to find the shortest route to a destination city in order to get a short time to get to that city and save time and costs on the way. The completion of the search for the shortest route uses the TSP concept. Basic concepts in running CSR 1. The journey starts and ends in the same city as the original city of the salesperson. 2. Entire cities must be visited without missing a single city.3. Sales are not allowed to return to the city of origin before all cities have been visited. By using this method, the distance between each city will be analyzed. The cities that the salesman will go to consist of 4 cities A, B, C, and D with a combination process to obtain as many as 24 lanes that can be passed by the salesman. From each route taken by the salesman, there are 2 shortest paths that can be used as alternatives, including the CABD=17+15+19=51 route and the DBAC=19+15+17=51 route. The final results of this study can be used as a reference in determining the shortest route by salesmen with a distance value of 15.